STRATEGI PENGEMBANGAN KAWASAN PERDESAAN DESA PULAU MADINAH KECAMATAN KUANTAN HILIR - Ria Asmeri Jafra (JURNAL PLANOLOGI DAN SIPIL (JPS), 2023)
The Rural Area is an area needs to be developed so that the village can increase income for the village society, because village has wide agricultural land. Thus a strategy needs to be carried out to develope the area, so that rural area has function optimally and can improve the standard of living of the society. The aim of this study was to obtain a strategy Development of Rural Areas of Pulau Madinah, Kuantan Hilir by using the SWOT method and to know the direction of development of the Area. The results of this study are necessary to optimize the function of the land, the construction of road infrastructure and irrigation, making processed food and beverages and using appropriate energy in processing land. The direction of the development of the Rural area of ​​Pulau Madinah through the empowerment of rural society by maintaining the area of ​​agricultural land